Agama Lokal Pribumi Sasak (Menelusuri Jejak “Islam Wetu Telu” di Lombok) - Retno Sirnopati (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2021)
The term Islam Wetu Telu is still controversial because the term is considered to be made up by colonialism to divide Islam in Lombok. Thus, the original religion of the Sasak tribe needs to be explored and studied so that the local people of Lombok understand the origins of religion and its cultural roots. The term Wetu Telu is generally understood as the belief of the local Sasak community who have not received a full understanding of Islam. The explanation of Wetu Telu will be described based on the views or opinions of insiders and outsiders. This paper will describe the traces of Islam wetutelu; traces and developments in Gumi Sasak Lombok. This paper is a literature review by examining some of the main references from previous research on Sasak Islam located on the island of Lombok. From the results of the study, it is concluded that Wetu Telu, which is considered a local belief of the Sasak people of Lombok, is a syncretic form of the previous belief (Hindu-Buddhist-Boda) which is often confronted with the Islamic belief of Time Lima. Outsiders only look at the terminology aspect which is often different from the understanding of the Wetu Telu adherents themselves so that there is a misunderstanding of the meaning of Wetu Telu. As for Wetu Telu adherents, the term is only a symbolic one that has a broad meaning and interpretation